Motivation Cards to Support Students' Understanding on Fraction Division - Wahyu, Kamirsyah; Amin, Siti Maghfirotun; Lukito, Agung (Universitas Ahmad Dahlan, 2017)
This design research aims to develop a learning activity which supports the fifth-grade students to understand measurement fraction division problems (A whole number divided by a fraction that result in a whole number answer) conceptually. Furthermore, how students solve the fraction division problem using models is also analyzed. Data for the retrospective analysis is collected through two teaching experiments in the form of students' work, field notes, and some part of classroom discussions. The important findings in this research are: 1) the developed learning activity namely Motivation Cards support students understand that 3 divided by one-half means how many one-half are in 3 through models. However, when the divisor is not a unit fraction they could not directly relate the unshaded part in area model for example. 2) area model is proper model to be firstly introduced when the students work on fraction division. 3) understanding this kind of fraction division help students understand other measurement fraction division where both divisor and dividend are fractions. 4) the learning activity supports the development of character values for students.